Azolla’s cultivation with rainwater and its effect on milk yield and quality - K, Giridhar; Arangasamy, A.; Pal, D. T.; Devi G., G. Letha; Mech, A.; Kataktalware, M. A.; Chaithra, G. J. (Indian Farming, 2025)
Azolla is a free floating water fern. It can be grown with just rainwater, without addition of soil, dung or phosphorus. Among different species of genus Azolla, A. pinnata is popular. The higher crude protein content (over 23%) as well as presence of essential amino acids (lysine), vitamins like A and B12 and minerals like calcium, phosphorous, potassium and magnesium made Azolla a useful feed supplement for livestock. Daily feeding of one kg of fresh Azolla increased average milk yield by half a litre per cow besides improving the fat content.